The Measurement of Human Resources Employees by using Human Resources Score Card Method and Analytical Hierarchy Process Method - Sutrisno Sutrisno; Healthy Aldriany Prasetyo; Adriana Ina Faot (Budapest International Research and Critics University, 2022)
In a company engaged in the maintenance of LPG gas cylinders, it is customary to check for Retest, Repaint, and Retest Repaint tubes. The operation is performed by checking and classifying the maintenance of LPG cylinders to determine whether they are defective. The company has 25 employees in the workshop section and 8 people in the administration or office division with working hours in this company from morning to evening. However, several problems can affect the performance of human resources including employees who work in this company lack of discipline, such as there are still employees who are not present on time or late and even absent more than the specified day. Thus, this study measures the performance of human resources to determine the indicators that need to be improved. The method used in this research is the Human Resources Scorecard method and the Analytical Hierarchy Process method. The employee performance measurement’s calculation determined by the results of the HRSC method. The results of the questionnaire tested for validity and reliability testing. The result shows that the Compensation Perspective is the most important criterion for Human Resource Performance Measurement with a weighted value of 0.41 or 41%. Then, followed by the Personal Perspective criterion with a weighted value of 0.38 or 38%, then the Perspective Alignment criteria with a weight value of 0.14 or 14% while the Perspective High Performance criteria with a weight value of 0.07 or 7%.